Assessment of periodontal status in adults with diabetes mellitus - Deheriya, Manish; Bhargava, Anuj; Pippal, Dushyant; Ahirwar, Anupama (International Journal of Research in Medical Sciences, 2020)
Background: Diabetes mellitus is a group of chronic metabolic disorders known to exhibit a myriad of complications over a period of time. Periodontal disease is the sixth most common complication in diabetic patients. The aim of the study was to assess the periodontal status of adult diabetic patients. Methods: 100 diabetic patients in the age group of 25-80 years fulfilling the inclusion criteria were examined by a calibrated WHO CPI probe to assess their periodontal status as per the scoring criteria of the community periodontal index. Student t test, Chi square test and ANOVA F were applied for statistical analysis. p>0.05 was considered not significant and p<0.01 was considered highly significant. Results: A prevalence of 73% periodontitis was found in diabetic study population with statistically high significance (p=0.001) found according to age. A total of 52% Shallow pockets and 15% Deep pockets were reported respectively in middle (41-56 years) and older (57-80 years) age groups. Further, 47% male population was found to have statistically significant (p=0.027) more periodontitis (shallow and deep periodontal pockets) compared to female (26%) population. Conclusions: Within limitations of the study it may be safely concluded that assessment of periodontal status of DM patients revealed chronic periodontal destruction particularly in age groups beyond 40 years in majority of study population depicting that age is significantly associated with the increased prevalence and severity of periodontal disease in patients with diabetes.